(untitled) (Mongolian Journal of Arts and Culture, 2025)
This article delves into the challenges facing mass communication in the digital age, critically examining how emerging trends are reshaping media systems, public discourse, and societal structures. It explores key concepts like tabloidization, infotainment, and clickbait, shedding light on how the drive for audience engagement and profit often comes at the expense of factual depth and public trust in journalism. The discussion extends to structural concerns such as media consolidation, the decline of local journalism, and the emergence of “news deserts,” illustrating their impact on the diversity and inclusivity of information available to the public. Using theories like agenda-setting and false balance, the article critiques how mass media can influence societal narratives, often favoring sensationalism or oversimplified stories of conflict. It also investigates the role of technology in shaping media dynamics, focusing on issues like surveillance capitalism, algorithm-driven polarization, and the creation of filter bubbles. These mechanisms, including techniques like browser fingerprinting, are shown to affect what content audiences see and how public opinion is formed. Public engagement in the digital space is analyzed through concepts like slacktivism, online dogpiling, and rumor cascades, situating these behaviors within broader patterns of digital interaction. The article also tackles challenges like deplatforming, astroturfing, and ad clutter, emphasizing their effects on media accessibility, user experience, and the authenticity of public discourse. Frameworks such as the Overton Window, narrative fallacy, and deviancy amplification spiral are used to explore how media coverage influences public perception and drives moral panics. By bringing together these perspectives, the article calls for a reevaluation of media ethics, regulation, and audience education to better navigate the complexities of modern mass communication. It looks to deepen our understanding of the rapidly evolving media landscape while offering ideas for future research and practical solutions.